Risk of depressive disorders in women undergoing hysterectomy: A population-based follow-up study. (September 2015) - Chou, Po-Han; Lin, Ching-Heng; Cheng, Chin; Chang, Chia-Li; Tsai, Chia-Jui; Tsai, Ching-Pei; Lan, Tsuo-Hung; Chan, Chin-Hong
Abstract: Objective: The objective of this study was to assess the risk of depressive disorders in women who underwent hysterectomy in Taiwan. Methods: A retrospective study was conducted in a matched cohort of cases using the National Health Insurance Research Database of Taiwan. Database records from 1689 women who underwent hysterectomy between 2001 and 2005 were included in this study. A control group matched for age and physical comorbidity was selected from the same database (n = 6752). For all cases, medical records were tracked until the end of 2009 to identify whether a depressive disorder was diagnosed during the follow-up period. The hazard ratio (HR) for depression during the observation period was analyzed using multivariable Cox proportional-hazards models, adjusted for age, physical comorbidities, and other socioeconomic factors. Results: The HR for depression was 1.78 times higher for the group that underwent hysterectomy than for the control group (adjusted HR = 1.78; 95% CI = 1.46–2.18, p < 0.001). In addition, HR for major depressive disorder in women who underwent hysterectomy was significantly higher (1.84 times) than for the control group (adjusted HR = 1.84; 95% CI = 1.23–2.74, p < 0.01). Conclusions: Our study revealed that, in Taiwan, women who underwent hysterectomy had an increased risk of developing depression. Longitudinal studies to follow-up the psychological outcomes in Taiwanese women who underwent hysterectomy will be necessary to confirm our findings. Highlights: This study was conducted using National Health Insurance Database in Taiwan. We found an increased risk of depressive disorders in women undergoing hysterectomy. Psychological interventions may be needed for those patients.